Multiple papillary fibroelastomas attached to left ventricular side and aortic side of the aortic valve: A report of new case and literature review. Issue 6 (22nd May 2019) - Tsugu, Toshimitsu; Nagatomo, Yuji; Endo, Jin; Kawakami, Takashi; Murata, Mitsushige; Yamazaki, Masataka; Shimizu, Hideyuki; Fukuda, Keiichi; Mitamura, Hideo; Lancellotti, Patrizio
Abstract: The aortic valve (AV) is the most commonly affected site in multiple papillary fibroelastomas, but the frequency of embolism caused by the attachment side of the AV has not been elucidated. According to the review of the previous literature, 16 cases have been found attached to the AV. Of these, 6 of these have been found to be attached on the aortic side and 4 on the left ventricular side, 1 was bilateral, and 5 cases were unknown. Of the cases found on the aortic side, embolism occurred in 3 of them, and of the left ventricular side cases, embolism occurred in 2 of them. The frequency of embolism is equivalent even if papillary fibroelastoma attached to either side of the AV.